The effect of contextual variables in the relationship between CSR and CFP: Evidence from Indonesian companies - Fauzi, Hasan; Md. Idris, Kamil (Indonesian Center for Social and Environmental Research and Development, 2010)
The objectives of this study is to investigate whether business environment, business strategy, formalization, decentralization, reliance on combination of belief & boundary system, reliance on combination of diagnostic & interactive control system, reliance on interactive control system moderate the relationship between CSR and CFP under the slack resource and good management theories. 220 respondents from manufacturing companies listed on the Jakarta Stock Exchange were selected and two regression models were developed to examine the relationship between the related variables. The findings show that business environment has moderated the CSR-CFP link under good management theory, decentralization has moderated the CSR-CFP link under slack resource theory, and reliance on combination of diagnostic and interactive control system has moderated the CSR and CFP link based on slack resource theory.